Asthma control and care among six public health clinic attenders in Malaysia: a cross-sectional study - Hussein, Norita; Liew, Su May; Hanafi, Nik Sherina; Lee, Ping Yein; Cheong, Ai Theng; Ghazali, Sazlina Shariff; Chinna, Karuthan; Pang, Yong Kek; Kassim, Asiah; Parker, Richard A.; Schwarze, Jürgen; Sheikh, Aziz; et al. (John Wiley & Sons, 2023)
Background and Aims: Asthma is common in Malaysia but neglected. Achieving optimal asthma control and care is a challenge in the primary care setting. In this study, we aimed to identify the risk factors for poor asthma control and pattern of care among adults and children (5–17 years old) with asthma attending six public health clinics in Klang District, Malaysia. Methods: We conducted a cross-sectional study collecting patients’ sociodemographic characteristics, asthma control, trigger factors, healthcare use, asthma treatment, and monitoring and use of asthma action plan. Descriptive statistics and stepwise logistic regression were used in data analysis. Results: A total of 1280 patients were recruited; 85.3% adults and 14.7% children aged 5–17 years old. Only 34.1% of adults had well-controlled asthma, 36.5% had partly controlled asthma, and 29.4% had uncontrolled asthma. In children, 54.3% had well-controlled asthma, 31.9% had partly controlled, and 13.8% had uncontrolled asthma. More than half had experienced one or more exacerbations in the last 1 year, with a mean of six exacerbations in adults and three in children. Main triggers for poor control in adults were haze (odds ratio [OR] 1.51; 95% confidence interval [CI] 1.13–2.01); cold food (OR 1.54; 95% CI 1.15–2.07), extreme emotion (OR 1.90; 95% CI 1.26–2.89); air-conditioning (OR 1.63; 95% CI 1.20–2.22); and physical activity (OR 2.85; 95% CI 2.13–3.82). In children, hot weather (OR 3.14; 95% CI 1.22–8.11), and allergic rhinitis (OR 2.57; 95% CI 1.13–5.82) contributed to poor control. The majority (81.7% of adults and 64.4% of children) were prescribed controller medications, but only 42.4% and 29.8% of the respective groups were compliant with the treatment. The importance of an asthma action plan was reported less emphasized in asthma education. Conclusion: Asthma control remains suboptimal. Several triggers, compliance to controller medications, and asthma action plan use require attention during asthma reviews for better asthma outcomes.